ANALISIS IMPLEMENTASI PENGGUNAAN UANG PERSEDIAAN MELALUI KKP DALAM PELAKSANAAN BELANJA PEMERINTAH - Ananda Arsyad, Nur Dhea; Tuli, Hartati; Aqmal, Ikhlas Ul (Jurnal Riset Terapan Akuntansi, 2025)
This study analyzes the implementation of the use of Petty Cash (Uang Persediaan/UP) through the Government Credit Card (Kartu Kredit Pemerintah/KKP) in government expenditure at the Regional Office of the Directorate General of Treasury (Kanwil DJPb) in Gorontalo. The main issues examined include the effectiveness, efficiency, and challenges in adopting KKP as a payment instrument for government operational expenses. This study aims to evaluate how KKP usage enhances transparency, accountability, and state financial management. A qualitative approach with a case study method was employed, involving interviews, observations, and document analysis. The findings indicate that KKP implementation benefits transaction speed and reduces cash management risks. However, challenges remain, such as limited user understanding, resistance to change, and inadequate supporting infrastructure in certain areas. These findings provide recommendations for the government to improve KKP policy effectiveness for optimizing in Kanwil DJPb for state expenditure management. Keywords: Petty Cash, Government Credit Card, Government Expenditure, Effectiveness, Accountability